(untitled) (Baghdad Science Journal, 2016)
Gestational diabetes mellitus (GDM) is a complication of gestation that is characterized by impaired glucose tolerance with first recognition during gestation. It develops when ?- cell of pancreas fail to compensate the diminished insulin sensitivity during gestation. This study aims to investigate the relationship between mother adiponectin level and ?- cell dysfunction with development gestational diabetes mellitus (GDM) and other parameters in the last trimester of pregnancy. This study includes (80) subjects ( pregnant women) in the third trimester of pregnancy, (40) healthy pregnant individuals as control group aged between (17 - 42) years and (40) gestational diabetes mellitus patients with aged between (20 - 42) years. The following biochemical investigation is studied: oral glucose tolerance test (OGTT), adiponectin , insulin, C-reactive protein (CRP),body mass index (BMI), and homeostasis model assessment- insulin resistance (HOMA – IR). The adiponectin levels are significantly lesser in females who develop GDM than the control group (P?0.01), while the insulin and OGTT concentrations were significantly higher in females with GDM than control group (P?0.01).The concentrations of CRP are non significantly different between the females who develop GDM and the control group.Conclusions: Lower adiponectin concentrations are associated with an increased risk of the development of gestational diabetes mellitus and females, who develop gestational diabetes mellitus, have higher levels of insulin resistance from normal females, Obesity is a shape of persistent low grade inflammation which causes elevated concentrations of C- reactive protein.